Conceptualising change in marine governance: Learning from Transition Management. (September 2018) - Kelly, Christina; Ellis, Geraint; Flannery, Wesley
Abstract: Coastal states are increasingly urged to transform their sectoral and fragmented marine governance regimes, and to implement integrated and holistic management approaches. However, to be successful, integrated governance mechanisms, such as marine spatial planning and ecosystem-based management, will involve transformative change of institutions, values and practices. Although 'integration' is commonly championed as an important normative attribute of marine management by academics, policymakers and environmental groups, it is often done so with little consideration of the complexity of institutional context in which a shift to new management approaches takes place. This paper reviews the most cited academic papers in the field of marine governance, showing that most overlook many of the key institutional challenges to integration, often derived from issues such as incumbency, path dependency, policy layering and other pragmatic strategies. While integrated management approaches have a normative capacity to fundamentally transform marine governance, the failure to understand the institutional dynamics that may impede effective implementation, leaves much of the research in this field naively impotent. There is a need, therefore, to develop a more realistic understanding of the context in which transformative change takes place. It is argued that Transition Management has the potential to both conceptualise and operationalise strategies to address these barriers based on a long term perspective using a participatory process of visioning and experimentation. Highlights: The sustainable management of marine resources is a pressing issue for coastal states. Integrated approaches are often promoted as a key step in achieving sustainability. Key institutional barriers continue to impede integrated marine management. Most cited papers on marine governance fail to address the transformative change needed. Transition Management offers real potential for transformative marine governance.